ENHANCEMENT OF DURABILITY OF TRACTOR SUSPENSION AXLES - Doshchechkina, I.; Tatarkina, I.; Storchak, O.; Дощечкина, И. В.; Татаркина, И. С.; Сторчак, О. Г.; Дощечкіна, І. В.; Татаркіна, І. С.; Сторчак, О. Г. (Харьковский национальный автомобильно-дорожный университет, 2017)
The ‘soft’ nitriding of the suspension axle surface of the T150K tractor at the depth of 0.08 mm enables us to enhance its constructive strength, to increase its service life by 25 % and have a considerable economic effect.
ПОВЫШЕНИЕ ДОЛГОВЕЧНОСТИ ОСЕЙ СИСТЕМЫ ПОДВЕСКИ ТРАКТОРА
ПІДВИЩЕННЯ ДОВГОВІЧНОСТІ ОСЕЙ СИСТЕМИ ПІДВІСКИ ТРАКТОРА
Keywords: steel; surface; nitriding; layer thickness; core; tension test; deformation; destruction; strength; flexibility; tractor suspension axle; service life increase; сталь; поверхность; азотирование; толщина слоя; сердцевина; испытание на растяжение; деформация; разрушение; прочность; пластичность; оси подвески трактора; эксплуатационный ресурс; поверхня; азотування; товщина шару; серцевина; випробування на розтягування; деформація; руйнування; міцність; пластичність; осі підвіски трактора; експлуатаційний ресурс; 669.017: 621.73.